Salvation in death - Robb, J. D., 1950- (New York : G.P. Putnam's Sons, 2008)
The priest at a Catholic funeral mass brings the chalice to his lipsand falls over dead. When Detective Lieutenant Eve Dallas confirms that the consecrated wine contains potassium cyanide, she's determined to find out who committed this unholy act.
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Policewomen -- Fiction; Priests -- Crimes against -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction